Act of revenge [compact disc, unabridged] : a novel - Brown, Dale, 1956-; DeFelice, Jim, 1956- (Brown, Dale, 1956- Puppet master series, 2018)
When terrorists attack Boston, Louis Massina races against time to save the city with a high-tech counteroffensive